Endothelium damage and vasoregulating activity of vascular wall in patients with rheumatoid arthritis - O. V. Inamova (Научно-практическая ревматология)
Objective. To study vasoregulating function circulating endothelial cells (CEC) number in blood of patients with rheumatoid arthritis (RA) with different activity and clinical features. Material and methods. 102 pts with RA aged 17 to 55 years were examined. RA was diagnosed according to ACR criteria. Mean disease duration was 7,2+0,6 years. 29 pts had I, 59 - II and 17 - 111 activity degree. 17 pts had Raynaud’s syndrome. Control group consisted of 26 healthy volunteers. Endothelium damage was assessed by CEC content in peripheral blood according J. Hladovec method. Vasoregulating function of vascular wall was assessed by flow-dependent and nitroglycerine-induced dilatation. Results. Flow-dependent vasodilatation was decreased (p<0,02) and CEC number was increased (p<0,01) in RA pts comparing with control group. Endothelium damage degree and vascular tone regulation disturbances depended on activity, presence of systemic features and duration of RA. Conclusion. Blood CEC number measurement can be used for assessment of endothelium damage in RA. Pts with RA have disturbance of vasoregulating function of endothelium and its degree depends on activity and duration of the disease.